Incentive Funding Meets Incentive-Based Budgeting: Can They Coexist? - Lang, Daniel (Canadian Journal of Higher Education, 2017)
Two major developments in the financial management of higher education have occurred more or less contemporaneously: incentive or performance funding on the part of government and incentive-based budgeting on the part of institutions. Both are based on fiscal incentives. Despite their several inherent and interconnected similarities, incentive funding and incentive-based budgeting have been viewed and appraised on parallel tracks. This study investigates their convergence. In doing so, it sharpens the definitions of both, identifies their respective track records, and discusses problems that are chronic to both. The study concludes that although incentive funding and incentive-based budgeting are sometimes at cross-purposes, they are functionally interconnected. The study uses Canada as an example because it is the jurisdiction that so far has seen the most extensive mutual deployment of performance funding and incentive-based budgeting.